Effect of weeding regime on weed vegetation and yield performance of wheat in two locations of Mymensingh district - Kabir, MG; Begum, M; Hossain, MM; Anwar, MP (Progressive Agriculture, 2015)
On-farm two experiments were carried out at the Fulbaria upazila under Mymensingh district and Agronomy Field Laboratory, Department of Agronomy, Bangladesh Agricultural University (BAU), Mymensingh during the period from November 2011 to March 2012. The experiment comprised ten fields for each of the locations which composed of three weeding regime treatments, namely, unweeded, farmers weeded and weed free. The design was randomized complete block with ten replications. Data on weed density, yield contributing characters and yield of wheat were recorded. Except straw yield in Fulbaria all others yield contributing characters were affected significantly due to weeding regime treatment. The highest grain yield was recorded in weed-free treatment compared to farmers weeded and unweeded treatment in Fulbaria. Whereas, in Agronomy Field Laboratory at BAU, the highest grain yield was observed in weed-free treatment which was statistically identical to farmers weeded treatment. Five dominant weed species were identified in Fulbaria naimly Cynodon dactylon L., Cyperus rotundus L., Alternanthera sessilis L., Polygonum orientale L. and Chenopodium album L. and in Agronomy Field Laboratory at BAU namely Gnaphalium affine L., Cyperus rotundus L., Digitaria sanguinalis L., Cynodon dactylon L. and Panicum repens L. Infestation of Cynodon dactylon L. was more in Fulbaria due to control difficulties and Gnaphalium affine L. was more in BAU due to weed seed bank year after year and poor cultural management. So there is scope to increase yield potential of wheat by improving existing weed control practices. Progress. Agric. 2014. 25: 23-30